FRI0511 Secukinumab demonstrates consistent safety over long-term exposure in patients with psoriatic arthritis and moderate-to-severe plaque psoriasis: updated pooled safety analyses. (15th June 2017) - Mease, PJ; McInnes, IB; Reich, K; Nash, P; Andersson, M; Abrams, K; Pricorp, L; Fox, T
Abstract : Background: Pooled safety data from secukinumab psoriasis (PsO) and psoriatic arthritis (PsA) clinical trial programs after ∼1 year of exposure have been reported. 1, 2 Objectives: To report updated longer-term secukinumab exposure safety data from PsO and PsA studies (data cut-off: 25 June 2016). Methods: The PsO data pool consisted of 9 Phase III studies in moderate-to-severe plaque PsO and PsA pool consisted of 3 Phase III studies in active PsA. Secukinumab doses differed in the studies and included intravenous (up to 10 mg/kg) or subcutaneous (s.c.; 75–300 mg) loading, followed by s.c. maintenance dosing (300, 150 or 75 mg). Placebo patients were re-randomised to secukinumab at 12–24 weeks depending on study design. Only data for approved secukinumab 300 and 150mg doses were included in analysis. Exposure adjusted incident rates (EAIR) were used to adjust for differences in exposure. Results: In both PsO and PsA, the most frequently reported adverse events (AEs) with secukinumab were non-serious infections of the upper respiratory tract, headache and arthralgia (Table). The EAIRs of AEs of special interest with secukinumab including Crohn's disease, Candida infections, serious infections, inflammatory bowel disease, major adverse cardiac events and neutropenia (reported in the Table) were similar in both PSO and PsA indications, and comparable to those reported previously. 1, 2 No cases of tuberculosis (new onset or reactivation) were reported. Conclusions: The safety profile of secukinumab was similar for PsO and PsA patients supporting its long-term use in these chronic conditions. Secukinumab long-term exposure safety data is consistent with that previously reported with shorter-term exposure, including being well tolerated, and without any new safety signals identified. References: Van de Kerkhof PC, et al. J Am Acad Dermatol 2016;75:83–98. Mease PJ, et al. Arthritis Rheumatol 2015; 67:A2886. Disclosure of Interest: P. Mease Grant/research support from: AbbVie, Amgen, Biogen Idec, BMS, Celgene, Crescendo, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, Biogen Idec, BMS, Celgene, Covagen, Crescendo, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, Biogen Idec, BMS, Crescendo, Janssen, Lilly, Pfizer, and UCB, I. McInnes Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, K. Reich Grant/research support from: AbbVie, Amgen, Biogen, Boehringer Ingelheim Pharma, Celgene, Centocor, Covagen, Forward Pharma, GlaxoSmithKline, Janssen-Cliag, Leo, Lilly, Medac, Merck Sharp and Dohme Corp., Novartis, Ocean Pharma, Pfizer, Regeneron, Takeda, UCB Pharma, Xenoport, Speakers bureau: AbbVie, Amgen, Biogen, Boehringer Ingelheim Pharma, Celgene, Centocor, Covagen, Forward Pharma, GlaxoSmithKline, Janssen-Cliag, Leo, Lilly, Medac, Merck Sharp and Dohme Corp., Novartis, Ocean Pharma, Pfizer, Regeneron, Takeda, UCB Pharma, Xenoport, P. Nash Grant/research support from: AbbVie, Amgen, BMS, Celgene, Eli Lilly, Hospira, MSD, Pfizer, Janssen, UCB, Novartis, Roche; Consultancy fees: AbbVie, Amgen, BMS, Celgene, Eli Lilly, Hospira, MSD, Pfizer, Janssen, UCB, Novartis, Roche, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Eli Lilly, Hospira, MSD, Pfizer, Janssen, UCB, Novartis, Roche, M. Andersson Employee of: Novartis, K. Abrams Shareholder of: Novartis, Employee of: Novartis, L. Pricorp Shareholder of: Novartis, Employee of: Novartis, T. Fox Shareholder of: Novartis, Employee of: Novartis